The Data Analytics Journey: Interactions Among Auditors, Managers, Regulation, and Technology* - Austin, Ashley A.; Carpenter, Tina D.; Christ, Margaret H.; Nielson, Christy S. (Contemporary Accounting Research, 2021)
ABSTRACT Data analytics is transforming our global markets and significantly impacting the financial reporting environment. We investigate how auditors, company managers, and regulation interact with data analytics and one another to affect the diffusion (i.e., development and spread) of data analytics throughout the financial reporting environment. We interview company managers and their audit partners, as well as additional stakeholders, including regulators. We interpret findings from our interviews using theory that highlights the importance of dynamic interactions between people and their environments, which include the prevailing rules (e.g., regulatory guidance). Our findings contribute to the accounting literature and practice by revealing three areas of conflict emerging from stakeholders' disparate preferences for data analytics. First, we uncover growing tensions between managers and audit partners regarding audit fees. Second, we find that managers and auditors believe the lack of accounting regulation specific to data analytics causes confusion and frustration. Finally, auditors report that they strategically leverage data analytics to provide clients with business‐related insights. However, regulators voice concerns that this practice might impair auditor independence and reduce audit quality. These areas of conflict suggest a need to revisit key tensions surrounding the audit function in a contemporary context characterized with significant technological shift.